Pertumbuhan dan Kandungan Karaginan Rumput Laut (Eucheuma) pada Spesies yang Berbeda - Anton Anton (Jurnal Airaha, 2017)
The Research aims to identify the species of Eucheuma that produce the best growth and caraginan content. The research method used is experimental design with this floating method with long line system. Analysis of the experiment using Completely Randomized Design (RAL) with 3 treatments namely; Sp 1 (E.cottoni), Sp2 (E.spinosum), and Sp3 (E.edule) each of 3 replications. Observed made are growth and caraginan content of each species by water quality parameters such as temperature, salinity, pH, current, nitrate, phosphate and water brightness. The results showed that the cultivation of Eucheuma seaweed from different species significantly affected the daily growth rate during the 6 weeks of the study period. BNT test results showed that all treatments were significantly different at 5% (P <0.05). The daily growth rate at the end of the study was highest at Sp2 (E.spinosum) treatment of 4.20%, second order of Sp3 (E.edule) treatment was 3.43% and the lowest in Sp1 (E.cottonii) treatment 1.90%. The analysis of the variety of caraginan content of Eucheuma seaweed from different species at the end of the study showed a very real effect. Furthermore, the effect on the BNT test results showed that all treatments were significantly different at the 5% level (P <0.05). The highest content of caraginan is Sp 1 (E.cottoni) equal to 61,54%, then Sp3 (E.edule) equal to 54,56% and the lowest at treatment of Sp2 (E.spinosum) equal to 46,64%.